APLIKASI PEMBELAJARAN BAHASA LATIN TUMBUH-TUMBUHAN BERBASIS ANDROID - Alfisyahri, Suciani; Simanjuntak, Pastima (Computer Science and Industrial Engineering, 2020)
Plants one of the living things that produce their own food, plants can convert sunlight into energy through photosynthesis. Based on research (Nia Kurniawati, 2015) in Indonesia there is a high diversity of flora and fauna, it is estimated that there are 100 to 150 families of diversity of plants and most of them potentially can be utilized. Latin is learned in the eyes of biological studies which are learned during junior high school. In the study of natural science, the names of plants, animals, as well as organs of the human body and animals that are given Latin. Middle school students usually learn Latin using guidebooks, there are no interactive and interesting applications suitable for junior high school students that can be easily understood by them, the teacher considers Latin material difficult for students to understand due to foreign languages ​​and are rarely heard. Android is one of the most widely used operating systems today, Android is free to use, modify, repair, and distribute by software developers, with the Android-based plant learning application for Android makes it easier for students to learn Latin, with voice features , pictures and descriptions make it easy for students to learn Latin for plants